Nitric oxide and reactive oxygen species: Clues to target oxidative damage repair defective breast cancers. (May 2016) - Somasundaram, Veena; Nadhan, Revathy; K. Hemalatha, Sreelatha; Kumar Sengodan, Satheesh; Srinivas, Priya
Abstract: The identification of various biomolecules in cancer progression and therapy has led to the exploration of the roles of two cardinal players, namely Nitric Oxide (NO) and Reactive Oxygen Species (ROS) in cancer. Both ROS and NO display bimodal fashions of functional activity in a concentration dependent manner, by inducing either pro- or anti- tumorigenic signals. Researchers have identified the potential capability of NO and ROS in therapies owing to their role in eliciting pro-apoptotic signals at higher concentrations and their ability to sensitize cancer cells to one another as well as to other therapeutics. We review the prospects of NO and ROS in cancer progression and therapy, and analyze the role of a combinatorial therapy wherein an NO donor (SNAP) is used to sensitize the oxidative damage repair defective, triple negative breast cancer cells (HCC 1937) to a potent ROS inducer. Preliminary findings support the potential to employ various combinatorial regimes for anti-cancer therapies with regard to exploiting the chemo-sensitization property of NO donors.